Acetabular Remodeling After a Varus Derotational Osteotomy in Children With Cerebral Palsy. Issue 2 (March 2016) - Chang, Frank M.; Ma, Julie; Pan, Zhaoxing; Ingram, James D.; Novais, Eduardo N.
Abstract : Background: The optimal surgical intervention for hip dysplasia in cerebral palsy (CP) is controversial. The purpose of this study was to determine (1) whether an isolated varus derotation osteotomy (VDRO) for the treatment of CP hip dysplasia allows for acetabular remodeling as measured by acetabular depth ratio (ADR), (2) the predictive factors for acetabular remodeling after an isolated VDRO for the treatment of CP hip dysplasia, and (3) to establish the normal ADR in typical children for comparison. Methods: Eighty-seven CP patients (174 hips) treated with an isolated VDRO between 2003 and 2009 were retrospectively reviewed. The average age at surgery was 4.6 years (range, 2.4 to 10.6 y) and the average follow-up period was 5.1 years (range, 1.1 to 9.9 y). Acetabular remodeling was assessed on radiographs by the ADR. Changes in preoperative and postoperative ADR were analyzed using linear mixed-effects models. Patients were divided into 2 different groups for the postoperative ADR analysis: Gross Motor Function Classification System (GMFCS) levels I, II, and III compared with GMFCS levels IV and V. The progression of ADR versus age was determined in a set of 917 normal children (1834 hips) for comparison. Results: There was a statistically significant increase (improvement) in ADR postsurgically for the collective CP set ( P <0.001) and for both GMFCS categories (I/II/III, IV/V: P <0.001). GMFCS level, sex, and intraoperative neck shaft angle (NSA) were determined to be significant predictors for postoperative ADR improvement. GMFCS level was the most significant predictor for an increase in ADR after surgery ( P <0.001). Less improvement in ADR was observed in patients of GMFCS levels IV and V compared with patients of GMFCS levels I, II, and III ( P <0.001). A lower intraoperative NSA resulted in greater postoperative increase in ADR ( P <0.05). Conclusions: Overall, isolated VDRO allowed for acetabular remodeling in CP hip dysplasia. Acetabular remodeling was increased in patients of GMFCS levels I, II, and III compared with patients of GMFCS levels IV and V. Increased varization at the time of VDRO improved acetabular remodeling. This study recommends considering GMFCS level and intraoperative NSA during surgical planning for CP hip dysplasia. Level of Evidence: Level IV—retrospective study.